2000
DOI: 10.1007/s004210000271
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in motor unit discharge activity with force control training in young and older human adults

Abstract: Six young (aged 18-22 years) and six older (aged 66-76 years) healthy humans participated in a visually guided isometric force modulation training program designed to improve accurate control of force during ankle dorsiflexion. Isometric force and the discharge activity of motor units (MU) supplying the tibialis anterior muscle were sampled concurrently at the beginning of the study, following 2 weeks of force modulation training and again after a 4 week retention period which followed immediately. The initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
4
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 37 publications
11
89
4
7
Order By: Relevance
“…Keen et al (1994) found that 4 weeks of strength training with the first dorsal interosseous muscle with heavy load (80% of maximum) by 10 young adults (aged 18-27 years) reduced the force fluctuations during isometric contraction at 50% MVC. A study by Patten and Kamen (2000) found that the ability of 6 young adults (aged 18-22 years) to match a force trajectory requiring force modulation up to 60% MVC in the dorsiflexor muscles improved after 2 weeks of force-tracking tasks. These previous findings agree with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keen et al (1994) found that 4 weeks of strength training with the first dorsal interosseous muscle with heavy load (80% of maximum) by 10 young adults (aged 18-27 years) reduced the force fluctuations during isometric contraction at 50% MVC. A study by Patten and Kamen (2000) found that the ability of 6 young adults (aged 18-22 years) to match a force trajectory requiring force modulation up to 60% MVC in the dorsiflexor muscles improved after 2 weeks of force-tracking tasks. These previous findings agree with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have been observed in young adults. Patten and Kamen (2000) reported that the ability to match force trajectory in the dorsiflexor muscles improved after 2 weeks of force-tracking tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation presumably involves both intrinsic motoneuron properties (Christie and Kamen 2010;Piotrkiewicz et al 2007) and the magnitude and distribution of synaptic inputs (Earles et al 2001;Eisen et al 1996;Erim et al 1999;Kido et al 2004;Oliviero et al 2006;Patten and Kamen 2000), which together influence the transformation of synaptic inputs into trains of motor unit action potentials. The present findings suggest that the integration of synaptic inputs as the membrane potential approached voltage threshold for generating action potentials differed for the two groups of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Keen et al (1994) found that 4 weeks of strength practice with the first dorsal interosseous muscle with a heavy load (80% of maximum) in 10 young adults (aged 18-27 years) reduced force fluctuation during isometric contraction at 50% MVC. Patten and Kamen (2000) report that the ability of 6 young adults (aged 18-22 years) to match a force trajectory requiring force modulation up to 60% MVC in the dorsiflexor muscles improved after 2 weeks of isometric force modulation training. Table 1.…”
Section: Steadiness Practice Reduces Force Fluctuation and Postural Swaymentioning
confidence: 95%
“…For example, 2 weeks of practicing a steadiness task with a light load (10% of maximum) on the index finger reduces force fluctuations and the discharge rate variability of single motor units in the hand muscles of older adults (Kornatz et al, 2005); similar effects are observed in young adults. Patten and Kamen (2000) report that the ability to match force trajectory in the dorsiflexor muscles improves after 2 weeks of isometric force modulation training. However, the effect of low-frequency steadiness practice (1 day of practice per week) on force fluctuations during isometric contraction is currently unknown.…”
Section: Practice Reduces Force Fluctuation and Improves Human Movementmentioning
confidence: 98%